Combined genetic and chemical screens indicate protective potential for EGFR inhibition to cardiomyocytes under hypoxia - Heliste Juho; Jokilammi Anne; Vaparanta Katri; Paatero Ilkka; Elenius Klaus (United Kingdom, 2022)
The return of blood flow to ischemic heart after myocardial infarction causes ischemia-reperfusion injury. There is a clinical need for novel therapeutic targets to treat myocardial ischemia-reperfusion injury. Here we screened for targets for the treatment of ischemia-reperfusion injury using a combination of shRNA and drug library analyses in HL-1 mouse cardiomyocytes subjected to hypoxia and reoxygenation. The shRNA library included lentiviral constructs targeting 4625 genes and the drug library 689 chemical compounds approved by the Food and Drug Administration (FDA). Data were analyzed using protein-protein interaction and pathway analyses. EGFR inhibition was identified as a cardioprotective mechanism in both approaches. Inhibition of EGFR kinase activity with gefitinib improved cardiomyocyte viability in vitro. In addition, gefitinib preserved cardiac contractility in zebrafish embryos exposed to hypoxia-reoxygenation in vivo. These findings indicate that the EGFR inhibitor gefitinib is a potential candidate for further studies of repurposing the drug for the treatment of myocardial infarction.